Model of Needs-Based Professionalism Development in Military Academy Magelang - Hartono, Untung; Rachman, Maman; RC, Achmad Rifai; Prihatin, Titi (The Journal of Educational Development, 2019)
Lecturers are professional educators and scientists whose main task is to transform, develop, and disseminate science, technology and art through education, research, and community service. Therefore, lecturers are required to possess pedagogical, personal, social, and professional competencies. Article 60, Law No. 14/2005 concerning Teachers and Lecturers, requires lecturers to "improve and develop their academic qualifications and competencies in a sustainable manner in line with the development of science, technology and art". The obligation stated in this law must be carried out by lecturers, especially lecturers at the Military Academy Magelang. The findings of this study are (1) the policy of preparing lecturers' planning by institutions is still weak and not paying attention to aspects of mapping needs; (2) the implementation of lecturer competency management development activities is not based on aspects of fulfilling student service needs; (3) management development strategies for improving lecturer competency have not been well coordinated; (4) management supervision to improve professional competence of lecturers is less attention to management aspects; (5) fostering the development of professional competence of lecturers is not sustainable and takes into account the aspects of reward and punishment.